2007
DOI: 10.1089/cap.2007.0061
|View full text |Cite
|
Sign up to set email alerts
|

QT Interval and Dispersion in Very Young Children Treated with Antipsychotic Drugs: A Retrospective Chart Review

Abstract: This preliminary, naturalistic, small-scale study suggests that antipsychotic treatment, with or without methylphenidate, in very young children is not commonly associated with significant alterations of QT interval and dispersion, suggesting the relative safety of these agents in this unique age group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…The study showed that abnormal QT dispersion or T wave abnormalities were not significantly associated with antipsychotic treatment, but were associated with lithium therapy [33]. In another study conducted by Nahshoni et al [34], QT interval, QTd, and rate-corrected values were calculated before initiation of antipsychotic treatment and during the maintenance period of 12 children while 3 of them were concomitantly maintained on methylphenidate therapy. They found that QT interval, QTd, and their rate-corrected values were all within normal values both before and after successful drug treatment.…”
Section: Discussionmentioning
confidence: 98%
“…The study showed that abnormal QT dispersion or T wave abnormalities were not significantly associated with antipsychotic treatment, but were associated with lithium therapy [33]. In another study conducted by Nahshoni et al [34], QT interval, QTd, and rate-corrected values were calculated before initiation of antipsychotic treatment and during the maintenance period of 12 children while 3 of them were concomitantly maintained on methylphenidate therapy. They found that QT interval, QTd, and their rate-corrected values were all within normal values both before and after successful drug treatment.…”
Section: Discussionmentioning
confidence: 98%
“…36 In one study, it was determined that QTd and T-wave abnormalities were related with mood regulators, not with antipsychotic treatment. 37 In our results, none of the patients had mood-regulating drug use. They had left their antipsychotic treatment at least 1 month ago, and the treatment that was used was atypical antipsychotic treatment.…”
Section: Discussionmentioning
confidence: 44%
“…According to a previous report, the QTc interval was not changed with psychostimulant drugs like risperidone and clotiapine 18 . Similarly, recent reports investigating the effects of methylphenidate on the QTc interval showed a mild increase in heart rate and blood pressure, but no effect on the QTc interval [19][20][21] .…”
Section: Discussionmentioning
confidence: 97%